(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The significance of documenting social and religious myths, rituals, customs and traditions has been recognized and responded to, more so in our contemporary times. Within Cultural Studies, a growing multidisciplinary academic discipline, it becomes a very relevant enterprise. Such documentation has greater significance and implications in the multicultural Indian context. It is also much relevant to the precarious state of Indian nationalism which, as Shashi Tharoor posits, is founded on ‘the Idea of India’.